(untitled) (Scientific journal of the Fergana State University, 2025)
Currently, the chemical composition and biological activity of leaves of Prunus persica (L.) Batsch. cultivated in the Republic of Karakalpakstan, located in the Aral Sea region, are unstudied This article presents the results of the analysis of biological active substances in the leaves of Prunus persica (L.) Batsch. method liquid chromatography - mass spectrometry (LC/MS). It has been established that common peach leaves contain flavonoids (hyperoside, rutin, kaempferol, epigallocatechin, isorhamnetin, apigenin), organic acids (malic, citric, gallic) and furocoumarin (psoralen). The literature reports the anti-inflammatory, antioxidant and anti-cancer activities of these bioactive substances in the leaves of the common peach